(untitled) (International Journal of Innovative Technologies in Economy, 2022)
The LoRaWAN technology is repeatedly mentioned in connection with smart city initiatives, as it moves in the field of connectivity and IoT environment. This paper examines the role of LoRaWAN in smart city strategy and what vulnerabilities are known in the project using LoRaWAN. With help of a concrete use case of the city of Pforzheim (Germany), a SWOT model is set up and tested with experts. From this it can be deduced that the LoRaWAN technology is currently undergoing an interesting development but also has to overcome any hurdles in the urban environment.